Cultural Dimension of Community Based Forest Enterprise in Nepal: A Case of Handmade Paper Enterprise in Eastern Hill of Nepal - Rai, Jailab Kumar (Journal of Forest and Livelihood, 2025)
The economic potential of forest-based enterprise has remained an important issue of policy and academic studies and debates in Nepal. However, there is limited or no attention on cultural dimensions. This paper explores the cultural dimensions by focusing on the complementarities and/or contradictions between the culture of people and forest-based enterprise interventions. This paper, based on an ethnographic study of a handmade paper enterprise (between 2015 and 2019 in Sawa village in Tyamke-Mayum Rural Municipality in Bhojpur district in the eastern hill of Nepal), has attempted to discuss the interface between the cultural attributes of Rai people as a moral economy and the techno-bureaucratic processes of the community-based forest enterprise (CBFE) as a part of the global phenomenon of the neoliberal economy. The paper argues that the establishment and functioning of CBFEs in remote village is not only a socio-political process of expansion of state’s bureaucratic controls; but this processes, as a part and parcel of the expansions of neoliberal economic institutions and ideas, have also been displacing and/or destroying the indigenous way of local economy. The paper suggests that there is a need of further studies and evidence-based policy debates about the significance of integrating the indigenous way of the local economy and neoliberal economic institutions and ideas in new Nepal.